Safety evaluation of an extension of use of the food enzyme triacylglycerol lipase from the non‐genetically modified Rhizopus arrhizus strain AE‐TL(B) - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme triacylglycerol lipase (triacylglycerol acylhydrolase; EC 3.1.1.3) is produced with the non‐genetically modified Rhizopus arrhizus strain AE‐TL(B) by Amano Enzyme Inc. A safety evaluation of this food enzyme was made previously, in which EFSA concluded that this food enzyme did not give rise to safety concerns when used in two food manufacturing processes. Subsequently, the applicant requested to extend its use to include four additional processes and to revise the use levels. In this assessment, EFSA updated the safety evaluation of this food enzyme when used in a total of six food manufacturing processes. As the food enzyme‐total organic solids (TOS) are removed from one food manufacturing process, the dietary exposure to the food enzyme‐TOS was estimated only for the remaining five processes. Dietary exposure was calculated to be up to 0.086 mg TOS/kg body weight (bw) per day in European populations. When combined with the no observed adverse effect level reported in the previous opinion (1960 mg TOS/kg bw per day, the highest dose tested), the Panel derived a margin of exposure of at least 22,791. Based on the data provided for the previous evaluation and the revised margin of exposure in the present evaluation, the Panel concluded that this food enzyme does not give rise to safety concerns under the revised intended conditions of use.